2012
DOI: 10.1007/s00408-012-9440-6
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis: The Association Between HIV Infection and Extrapulmonary Tuberculosis

Abstract: Findings show evidence on the association between extrapulmonary tuberculosis and HIV, based on case control studies. Further studies to understand the mechanisms of interaction of the two pathogens are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
69
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 38 publications
10
69
2
4
Order By: Relevance
“…In a study conducted in Turkey, tuberculosis was found to be the most common cause of infectious reasons for fever of unknown origin (19). Tuberculosis has even been considered in the differential diagnosis of arthritis and of malignancies due to M. tuberculosis complex, which causes granulomatous lesions (15,(20)(21)(22). In light of these data, pulmonary tuberculosis patients, who are the main source of new pulmonary or extrapulmonary tuberculosis cases, should be diagnosed immediately.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Turkey, tuberculosis was found to be the most common cause of infectious reasons for fever of unknown origin (19). Tuberculosis has even been considered in the differential diagnosis of arthritis and of malignancies due to M. tuberculosis complex, which causes granulomatous lesions (15,(20)(21)(22). In light of these data, pulmonary tuberculosis patients, who are the main source of new pulmonary or extrapulmonary tuberculosis cases, should be diagnosed immediately.…”
Section: Discussionmentioning
confidence: 99%
“…10,17 In fact, EPTB is considered an AIDS defining disease. 18 HIV co-infection is associated with more severe forms of EPTB, such as disseminated and meningeal TB, and a higher risk of death. 19 Studies have shown that patients with EPTB tend to deteriorate more rapidly and have higher mortality rates as compared to patients with pulmonary TB.…”
Section: Introductionmentioning
confidence: 99%
“…Pneumocystis jiroveci was the most common respiratory disease, especially among females, while cerebral toxoplasmosis was the most commonly identified intracranial mass lesion. Extrapulmonary TB was more common than pulmonary TB, as previously reported in patients with very low CD4 counts (25). However, findings of such a low prevalence should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 48%